PENGARUH MEDIA KARTU BERGAMBAR TERHADAP KETERAMPILAN MENULIS PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Rahmah, Zhahirah; Azmy, Bahauddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is based on the large number of students who struggle with writing fluency and have low writing skills. The research was conducted to identify the effects of picture card media on the early writing ability of first-grade students at SDN Keboananom Sidoarjo. The study uses a quantitative approach with a quasi-experimental design and a posttest-only control design. All first-grade students at SDN Keboananom Sidoarjo are included in the population of this study. The sampling technique used is purposive sampling, with class I B as the experimental group and class I C as the control group. The data collection method applied is a posttest, which will be analyzed numerically using normality tests, homogeneity tests, and t-tests. Based on the research findings, it is concluded that the use of picture card media has an impact on the early writing skills of first-grade students at SDN Keboananom Sidoarjo. The analysis results show a sig. (2-tailed) value < 0.000, which means H0 is rejected and H1 is accepted.